THE CASE OF TRAUMATIC TRANSMISSION CHILD OF HUMAN IMMUNODEFICIENCY VIRUS - Yu. V. Ostankova; A. V. Semenov; M. A. Churina; A. P. Rosolovsky; E. V. Grebyonkina; T. N. Tkachenko; T. А. Zhandarmova; A. А. Totolian (Журнал инфектологии)
Aim.  Analysis of phylogenetic relationships of HIV  isolates obtained from a child 8 years old and HIV-positive parents to search for a possible source of infection.Materials and  methods. The  blood  plasma  samples of 3 patients (father, mother and child) HIV from Veliky Novgorod were used.  Presented in a group of patients were directed to conduct epidemiological investigation cases  of HIV-1 infection a child from a dysfunctional family.  In the present study we used  genotyping by direct  sequencing of the  site  of the polymerase gene  (pol) length of 1285 nt., The gene  encoding the protease (PR) length of 465 nt. and a portion of the reverse transcriptase (RT) gene length of 820 nt.Results. The study allowed the  identification of the  HIV virus in clinical  samples. HIV-1 subtype A1 (IDU-A) was detected in all cases.  Phylogenetic analysis of isolates, where the  control  samples using   HIV-1  isolates obtained  previously  from Veliky Novgorod, possible to identify grouped in a separate cluster  sample from the mother, father  and  child, which  makes it possible to conclude about  intrafamily HIV infected child  by  one  of his  parents. The  nucleotide identity  of the  samples obtained from the  mother  and  the  child, showed a higher percentage of similarity – 98.4%, compared with  the  identity of the  samples between the  father  and  the mother  and between father and child (96.2% and 94.2%, respectively). Differences natural  polymorphisms in  protease and reverse  transcriptase genes  of the parents and  the child are discussed. Conclusion. The analysis of phylogenetic relationships of HIV isolates showed that the source  of infection of the child 8 years old, born and  living  in socially  disadvantaged families with HIV-positive parents, is his mother. Way parenteral transmission of infection by random simultaneous trauma  in the mother  and child.Molecular phylogenetic analysis using  routine methods for determining the resistance of HIV to antiretroviral drugs allows  to investigate cases  of HIV infection, identifying the source of infection.